Tablets in kindergarten for learning and parental involvement - Laranjeiro, D. (2021)
Children in pre-school education may benefit from using tablet devices due to their portability, multitouch interaction and variety of age-appropriate educational apps. This paper describes a workshop in one kindergarten where children have used tablets and educational apps to carry out an educational activity - drawings and videos of their self-portrait. The results were shared with parents on a communication platform, as a strategy for parental involvement in kindergarten. The data presented was collected through direct observation of the children, observation of the contents posted on the platform, interview with the educator and focus group with the parents. Content analysis was used to treat data. The use of tablets and apps has encouraged children's interest and dedication in educational activities. Sharing children's work on the platform has led parents to participate, comment online and talk with children about their work, facilitating parental involvement. This study contributes to the research about the motivation, willingness and ease of young children to use tablets and apps in learning activities. It also supports that the main interest of parents in a communication platform with the kindergarten is to have access to their children's work and to know what they do during the day.